Trends in South Asian Linguistics - Sharma, Ghanshyam; Lowe, John J. (John Jeffrey), 1982-; Bhattacharya, Tanmoy; Borchers, Dörte; Chevillard, Jean-Luc; Everaert, Martin; Ghosh, Sanjukta; Hale, Mark; Kissock, Madelyn; Kumar, Rajesh; Lahiri, Bornini; Molina-Muñoz, Adriana; et al. (Trends in linguistics. Studies and monographs, 2021)
The field of South Asian linguistics has undergone considerable growth and advancement in recent years, as a wider and more diverse range of languages have become subject to serious linguistic study, and as advancements in theoretical linguistics are applied to the rich linguistic data of South Asia. In this growth and diversity, it can be difficult to retain a broad grasp on the current state of the art, and to maintain a sense of the underlying unity of the field. This volume brings together twenty articles by leading scholars in South Asian linguistics, which showcase the cutting-edge research currently being undertaken in the field, and offer the reader a comprehensive introduction to the state of the art in South Asian linguistics. The contributions to the volume focus primarily on syntax and semantics, but also include important contributions on morphological and phonological questions. The contributions also cover a wide range of languages, from well-studied Indo-Aryan languages such as Sanskrit, Hindi, Bangla and Panjabi, through Dravidian languages to endangered and understudied Tibeto-Burman languages. This collection is a must-read for all scholars interested in current trends and advancements in South Asian linguistics.